Investigasi Pengambilan Keputusan Gen Y (Second Generation Existing Priority Members) untuk Menjadi Nasabah Prioritas BCA di Pekalongan (Sebuah Studi Fenomenologi) - Christianto, Andreas Andy; Soesanto, Harry (Master of Management Diponegoro University, 2019)
Gen Y, which is often referred to as Generation Millennials, will soon dominate the composition of the world of work and business in Indonesia. This millennial generation has a significant difference with previous generations, especially about what influences are the basis of their purchasing decisions. The researcher specifically examined how this millennial generation decided to join as a BCA Priority customer, what factors influenced their decision. The researcher used the Qualitative research method with a phenomenological narrative approach. The reason for choosing this method is so that researchers can interact directly with the speakers, dig deeper so that they get a more comprehensive picture of them. There were 8 speakers in this study which were divided into 4 groups, namely 1. Parents and Children of Priority customers, 2. Parents of Priority customers, Children not Priority customers, 3. Parents not BCA customers, Priority customer Children,4. Parents and Children are not Priority customers, but are included in the Priority criteria. The results of this study indicate that millennial generation purchasing decisions are influenced by many factors that can be grouped into 2 things: factors that have been experienced, felt and fulfilled their needs, namely ease of transactions, privileges, special prices, business networks, and pride and other factors that are expectations what they want when they become priority customers, namely financial solutions and increasing their knowledge. The new finding in this study was that parents' factors turned out to play a very important role for Gen Y especially the second generation of priority customers to decide to become BCA Prioritas customers.